Meningkatkan Hasil Belajar Menyundul Bola Dalam Permainan Sepak Bola Melalui Model Pembelajaran Pemecahan Masalah (Problem Solving) Pada Siswa Kelas VIII MTS Negeri 1 Maluku Tengah - Risaldi; Hasbullah, Bahmid; Souisa, Mieke; Hattu, Mesak (Academy of Education Journal, 2024)
The problem in this study is whether the learning outcomes of heading the ball in a football game can be improved through the problem solving learning model? The purpose of this study is to find out the improvement of learning outcomes of heading the ball in football games through the problem solving learning model in grade VIII students of MTS Negeri 1 Central Maluku. The subjects of the study were 18 students in grade VIII. The research instruments used in this study include; rubric assessment of attitudes, knowledge and psychomotor. The results of the study showed that the learning outcomes of the first cycle with a total score of 1214 and learning completeness reached 66.30% or there were 10 students who completed out of 18 students. Student learning outcomes in cycle II with a total score of 1441 and learning completeness reached 80.05%. There was an increase in learning outcomes of 13.75%.